Kinetika Reaksi Pembentukan Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Terumbu Karang Melalui Proses Presipitasi - Dedeng Hermoyo; Yelmida Azis; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Hydroxyapatite (Ca10(PO4)6(OH)2) is a calcium phosphate compound that has been widely used as bone implant material due to its chemical composition which is identical with the natural bone. The aims of this study are to synthesize, characterize and determine the kinetic reactions of the synthesized hydroxyapatite from Precipitated Calcium Carbonate (PCC) coral reefs through the precipitation method. Synthesis of hydroxyapatite used the variation temperatures of 30oC; 40oC; 50oC; 60oC with the calcium to phosphate (Ca/P) ratio of 1,67 at pH 9 and 11. The reactants were stirred for 24 hours, where the samples were taken every 10 minutes at first hour to determine the rate of kinetic and aged for 24 hours. Concentration of Ca in filtrate was analysed by using AAS method. The synthesized hydroxyapatite was characterized by XRD and obtained a hexagonal crystalline structure with size in range of 20 - 25 nm. The kinetic of the synthesized hydroxyapatite followed the pseudo second order equation with the values of reaction rate constants (k) at pH 9 were 0,003 min-1; 0,0055 min-1; 0,0044 min-1; 0,0057 min-1; while for pH 11 were 0,0033 min-1; 0,0069 min-1; 0,0079 min-1; 0,0087min-1.Keywords: coral reefs, hydroxyapatite, PCC, precipitation, reaction kinetics